2016
DOI: 10.1136/acupmed-2015-010989
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Amnestic Mild Cognitive Impairment: A Meta-Analysis of Randomised Controlled Trials

Abstract: Objective Mild cognitive impairment (MCI) is a pre-dementia state; 5-10% of cases per year will evolve into dementia. MCI can be amnestic (AMCI) or non-amnestic. AMCI is associated with a higher risk of progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 23 publications
1
65
0
Order By: Relevance
“…Four of them were moderate quality, two of them were low quality, and four of them were very low quality, which was downgraded due to the RoB of the included literatures, inconsistencies, and imprecision of the treatment effect. Table 6 presents the characteristics of the four SRs [36][37][38][39] of nonpharmacological interventions using traditional Chinese medicine. The effects of acupuncture were only reported in, and the most recent search included studies published throughout 2016.…”
Section: Grade Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of them were moderate quality, two of them were low quality, and four of them were very low quality, which was downgraded due to the RoB of the included literatures, inconsistencies, and imprecision of the treatment effect. Table 6 presents the characteristics of the four SRs [36][37][38][39] of nonpharmacological interventions using traditional Chinese medicine. The effects of acupuncture were only reported in, and the most recent search included studies published throughout 2016.…”
Section: Grade Assessmentmentioning
confidence: 99%
“…The effects of acupuncture were only reported in, and the most recent search included studies published throughout 2016. 36 The SRs included data from 5 to 18 primary prevention trials with 565 to 1,095 participants. All four SRs performed a meta-analysis and reported safety.…”
Section: Grade Assessmentmentioning
confidence: 99%
“…e need for effective therapies treating MCI is increasing, and the potential effectiveness of acupuncture and herbal medicine for MCI is receiving attention. Numerous studies have reported that acupuncture is effective in treating MCI and can be an alternative and adjunctive treatment for MCI patients [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite some evidence of acupuncture for aMCI emerging, methodological quality is generally not high enough to produce convincing and suggestive results [9] . A rigorously designed randomized controlled trial aims to explore the e cacy and safety of acupuncture on aMCI is warranted.…”
Section: Introductionmentioning
confidence: 99%